2017
DOI: 10.4018/irmj.2017070101
|View full text |Cite
|
Sign up to set email alerts
|

Information Systems Quality and Success in Canadian Software Development Firms

Abstract: For years, firms have been investing millions of dollars in information systems (IS) to gain operational and strategic benefits. However, in most cases these expected benefits have not been realized because the software development community has been plagued with the delivery of low quality and unsuccessful information systems. Duggan and Reichgelt's information systems quality model was adapted with minor modifications to explore the impact of process maturity and people on IS quality in Canadian software dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
10
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(12 citation statements)
references
References 75 publications
2
10
0
Order By: Relevance
“…On the other hand, other scholars identify usability, reliability, functionality, performance efficiency, portability, and maintainability as important quality measurements [40], [46]. Similarly, several studies identify functionality, usability, reliability, performance efficiency, and maintainability as the most impactful measures of software quality [14], [41], [43], [45]. Consequently, functionality, usability, performance efficiency, reliability, and maintainability indicators are adopted for the evaluation of software quality in this study.…”
Section: Software Qualitymentioning
confidence: 94%
See 3 more Smart Citations
“…On the other hand, other scholars identify usability, reliability, functionality, performance efficiency, portability, and maintainability as important quality measurements [40], [46]. Similarly, several studies identify functionality, usability, reliability, performance efficiency, and maintainability as the most impactful measures of software quality [14], [41], [43], [45]. Consequently, functionality, usability, performance efficiency, reliability, and maintainability indicators are adopted for the evaluation of software quality in this study.…”
Section: Software Qualitymentioning
confidence: 94%
“…Likewise, software quality depends on effective synchronization of the software development processes, software quality control activities, cost, and time [12], [13], [42], [43], [59]. Additionally, the mediating effect of human capital on the relationship between structural capital and software quality has also been empirically substantiated [14], [49]. Therefore, structural capital positively affects software quality through human capital.…”
Section: Research Framework and Hypothesesmentioning
confidence: 98%
See 2 more Smart Citations
“…The [31] study points out that success of information systems depends on users" perceptions more than on their quality. A [32] study that reviewed 40 empirical studies on technology design concluded that user involvement matters for learning, adjusted design and increased sense of participation.…”
Section: Stakeholders' Involvementmentioning
confidence: 99%